2019
DOI: 10.3847/1538-4357/ab46ab
|View full text |Cite
|
Sign up to set email alerts
|

The M101 Satellite Luminosity Function and the Halo–Halo Scatter among Local Volume Hosts

Abstract: We have obtained deep Hubble Space Telescope (HST) imaging of 19 dwarf galaxy candidates in the vicinity of M101. Advanced Camera for Surveys (ACS) HST photometry for 2 of these objects showed resolved stellar populations and Tip of the Red Giant Branch (TRGB) derived distances (D∼7 Mpc) consistent with M101 group membership. The remaining 17 were found to have no resolved stellar populations, meaning they are either part of the background NGC 5485 group or are distant low surface brightness (LSB) galaxies. It… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
96
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(102 citation statements)
references
References 112 publications
(164 reference statements)
3
96
0
Order By: Relevance
“…Follow-up HST imaging of 19 dwarf galaxy candidates confirmed that DwA and Dw9 are M101 group members, verified by their TRGB distance, and that the remainder of their sample are all background objects . Using the collected M101 dataset, Bennet et al (2019) constructed a satellite luminosity function for M101 that is complete to M V ≈−8, and showed that M101 has a very sparse satellite population in contrast to the MW and M31. Further, Bennet et al (2019) speculated that this may be due to the relative isolation of M101, as a comparable system with few satellites, M94, has a similarly isolated environment (Smercina et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Follow-up HST imaging of 19 dwarf galaxy candidates confirmed that DwA and Dw9 are M101 group members, verified by their TRGB distance, and that the remainder of their sample are all background objects . Using the collected M101 dataset, Bennet et al (2019) constructed a satellite luminosity function for M101 that is complete to M V ≈−8, and showed that M101 has a very sparse satellite population in contrast to the MW and M31. Further, Bennet et al (2019) speculated that this may be due to the relative isolation of M101, as a comparable system with few satellites, M94, has a similarly isolated environment (Smercina et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Images are 0.6' × 0.6' for the new candidates; north is up and east is to the left. For contrast, in the bottom set of panels we show colorized HST cutouts from two confirmed M101 satellites presented inBennet et al (2019) -DwA (MV =−9.5) and Dw9 (MV =−8.2); these images are 1.0' × 1.0' due to the larger size of these objects. In this case, each dwarf shows a clear, associated point source overdensity, indicating that we are resolving it into stars.…”
mentioning
confidence: 99%
“…The Local Volume (D < 11 Mpc, Kraan-Korteweg & Tammann 1979;Karachentsev et al 2004Karachentsev et al , 2013 hosts over 30 large galaxies with total luminosities in excess of M tot ≈ −20 K mag. Several surveys have targeted the more prominent of these giant galaxies like M 83 (Müller et al 2015), Centaurus A (Crnojević et al 2014(Crnojević et al , 2016Müller et al 2017;Taylor et al 2018), and others (Merritt et al 2014;Karachentsev et al 2015;Javanmardi et al 2016;Park et al 2017;Smercina et al 2018;Bennet et al 2019;Carlsten et al 2020;Davis et al 2020). Furthermore, dwarf galaxy surveys reach even more distant galaxy clusters (Venhola et al 2017;Wittmann et al 2019), groups (Geha et al 2017;Cohen et al 2018;Habas et al 2020), and the field (Greco et al 2018;Prole et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Its LF seems to be inconsistent with predictions from highresolution dark matter simulations, having far too few satellites for such a massive galaxy. In addition, Bennet et al (2019) argued for a strong variation in the LF derived from the environments of the giant galaxies in the Local Volume. This scatter seems to be larger than what is expected from the concordance model (but see also Carlsten et al 2020 for a different view).…”
Section: Introductionmentioning
confidence: 99%
“…Follow-up observations of many dwarf galaxy candidates from some of these surveys with better instruments have revealed an unavoidable contamination of false detections, i.e. E-mail: oliver.muller@astro.unistra.fr by confusion with background galaxies, foreground galactic cirrus, or instrumental noise (Chiboucas et al 2013;Merritt et al 2016;Müller et al 2018Müller et al , 2019Bennet et al 2019). A prime example is the galaxy Cen 8/KK 198, which has been regarded as dwarf galaxy associated with the Centaurus group for more than two decades (Cote 1996;Jerjen et al 2000;Karachentsev et al 2013;Müller et al 2017), until VLT observations have uncovered it as a low-surface brightness spiral galaxy (Müller et al 2019(Müller et al , 2021.…”
Section: Introductionmentioning
confidence: 99%